Moderate Caloric Restriction Partially Improved Oxidative Stress Markers in Obese Humans - Kanikowska, Dominika (Antioxidants (Basel), 2021)
Oxidative stress and inflammation are implicated in obesity. Therefore, we investigated whether moderate and short-term calorie restriction (CR) reflects a real-life situation, mediates weight loss, and improves oxidative stress markers. We analyzed oxidative stress markers in patients with obesity undergoing moderate CR. Serum oxidative stress markers (myeloperoxidase (MPO), superoxide dismutase (SOD), catalase, total antioxidant status (TAS), and reactive oxygen species (ROS) (generation by endothelial cells in vitro)) were measured in 53 subjects (mean BMI 37.8 ± 5.9 kg/m(2)) who underwent 8 weeks of CR, which included a reduction of 300–500 kcal/day. MPO was the most CR-sensitive parameter. The mean level of serum MPO in patients with obesity was 20% higher than that in post CR intervention (p < 0.001). SOD increased by 12% after CR (p < 0.05), which was largely due to the improvement in glucose tolerance and the reduction in insulin resistance after CR. Other tested parameters were not modified during the treatment. CR resulted in an expected decrease in body weight (by 5.9 ± 4.6 kg, p < 0.0001) and other anthropometric parameters. Additionally, it was accompanied by a significant change in hsCRP, hsTNF alpha, hsIL-6, leptin (all p < 0.0001), and HOMA-IR (p < 0.05). Cardiovascular and metabolic parameters were also partially improved. Short-term, moderate CR partially improves antioxidant capacity but is enough to substantially change anthropometric parameters in obese patients. Our observations indicate that mimicking real-life situations and low-cost dietary intervention can be successfully implemented in obesity treatment with a simultaneous moderate effect on antioxidant status.